Investigation of rhythms of secretion and repeatability of plasma adrenocorticotropic hormone concentrations in healthy horses and horses with pituitary pars intermedia dysfunction. (30th August 2013) - Rendle, D. I.; Litchfield, E.; Heller, J.; Hughes, K. J.
Summary Reasons for performing study There is little published information on whether measurement of plasma ACTH concentration at a single timepoint is a repeatable indicator of pituitary pars intermedia dysfunction (PPID). Objectives To determine whether ultradian or circadian fluctuations in ACTH production influence plasma ACTH concentration in normal horses and horses with PPID. Study design Prospective observational study. Methods Plasma ACTH concentration in 8 non‐PPID horses and 8 horses with PPID was measured at 08.00, 11.00, 14.00 and 17.00 h on 5 nonconsecutive days within a 3 week period. In addition, at 08.30 h on one day, 6 samples were collected from each horse at precisely 5 min intervals over a period of 25 min. Descriptive and graphical analysis was performed and a linear mixed effects model was fitted to assess the effect of time of day on ACTH concentration in non‐PPID and PPID horses. Results Evidence of ultradian fluctuation in ACTH production was not identified in either non‐PPID or PPID horses. Evidence for circadian fluctuation was identified in non‐PPID horses; plasma ACTH concentrations were highest at 08.00 h and decreased through the day. There was no evidence of circadian fluctuation in PPID horses. In non‐PPID horses, the magnitude of circadian changes in ACTH concentration was smaller than variations in concentration that occurred at random. Intrahorse variability of ACTH concentration was greater in PPID horses than in non‐PPID horses. Conclusions Ultradian and circadian fluctuations in ACTH concentration are unlikely to influence clinical decision making; however, variations of potential clinical relevance do occur in individual horses, for reasons that remain to be determined, and increase in magnitude with progression of PPID. Results of the current study indicate that when an ACTH concentration between 19 and 40 pg/ml is measured, further testing should be considered to increase the accuracy of PPID diagnosis.